Anesthetic Management for Multiple Family Members with Myotonic Dystrophy for Interventional Cardiac Procedures—A Case Series - Gorelik, Leonid; Flores, Antolin (Frontiers in Medicine, 2018)
Myotonic Muscular Dystrophy (MMD) is a rare autosomal dominant disorder that can complicate anesthetic management of patients. MMD is characterized by progressively worsening muscle loss and weakness, cardiac conduction abnormalities, cardiomyopathy, restrictive lung disease, obstructive sleep apnea, and delayed gastric emptying. Patients presenting with MMD for any surgical procedure present a management challenge to the anesthesiologist. Several reports of airway loss due to medication mediated respiratory depression, sudden death due to dysrhythmias, aspiration of stomach contents, and prolonged intubation have been reported. We present a case series of three family members with MMD type 1 who presented for electrophysiologic assessment of the cardiac conduction system and possible pacemaker insertion. While there are reports of anesthetic management of patients with myotonic dystrophy for various procedures, our report is unique in that we were able to demonstrate variations of anesthetic management based on the procedure and variation in disease phenotype – differing severity between family members.